Successful Treatment of Refractory and Relapsed CNS Acute Lymphoblastic Leukemia With CD-19 CAR-T Immunotherapy: A Case Report - Htun, Kyaw Thu; Gong, Qiang; Ma, Le; Wang, Ping; Tan, Ya; Wu, Guangsheng; Chen, Jieping (Frontiers in Oncology, 2021)
In recent decades, survival was significantly improved in B cell acute lymphoblastic leukemia (B-ALL) patients. But refractory and relapsed B-ALL still has aggressive clinical behavior and poor prognosis. Especially, the patients with central nervous system infiltration is very difficult to achieve complete remissions with routine treatment. Chimeric antigen receptor-modified T-cell therapy targeting CD-19 has shown to be a beneficial treatment approach in refractory and relapsed B cell acute lymphoblastic leukemia (r/r ALL). However, there are very few studies reporting to treatment of refractory and relapsed B cell ALL with central nervous system infiltration. Here, we reported one single case of a patient diagnosed with relapsed B cell ALL with CNS infiltration who was successfully treated by second generation CAR containing a co-stimulator CD28 or 4-1BB therapy. Long-term proliferation of CAR-T cells in peripheral blood and bone marrow was observed more than 18 months. After CAR-T treatment, the patient got toxicity of grade 1 cytokine release syndrome and achieved significantly 36 months event free survival of follow-up. It is suggested that CD-19 CAR containing CD28 or 4-1BB costimulatory may be an effective therapy in refractory and relapsed B cell ALL with central nervous system infiltration. Its toxicity is mild, and its safety is high. Clinical Trial Registration:ClinicalTrials.gov Identifier: NCT02349698.